On the Formation of Old Armenian Dipthongs and Dipthongal Structures (Synchronic analysis) - Petrosyan, Vardan (Bulletin of Yerevan University B: Philology, 2023)
The distinction of Old Armenian (OA) diphthongs and diphthongal structures has always been one of the most controversial issues in Armenological studies. Their quantitative, as well as qualitative nature may be dependent on the criterion the distinction is based upon.The application of various criteria to these constituents results in the distinction between diphthongs, diphthongoids and triphthongoids  and their classification into stable and non-stable types. The first group is made up of the elements which, regardless of the word transformation (declension, conjugation, compounding) are always uttered in the same syllable and refer to the same morpheme. The second group contains the ones whose diphthongal/ triphthongal nature is conditioned by their position in the chain. It noteworthy that owing to the division or change in the phonemic chain, its elements can find themselves in different syllables or can be divided by a morphemic seam. Among the OA diphthongs only եա (ea) was stable which, when viewed from a phonemic perspective,  was equivalent to one complex phoneme. The rest were non-stable diphthongal structures. Most, if not all diphthongoids and tripthongoids fall into the stable group. The application of the above-mentioned criteria makes it possible to distinguish 1 stable, 7 non stable dipthongs, 15 diphthongoids and 15 tripthongoids in Old Armenian.
Keywords: stable diphthongs; non-stable diphthongs; diphthongoids; syllable distribution; morphological criterion; morphemic seams